ADMINISTRATIVE TRANSPARENCY IN THE ERA OF OPEN GOVERNMENTS - Saif raad Saad alimami (International Journal of Business, Law and Political Science, 2026)
Objective: This study addressed the topic of administrative transparency as one of the most important modern mechanisms for improving public administration performance and combating corruption. Method: The conceptual framework of transparency was discussed by defining it, explaining its elements and dimensions, in addition to highlighting its importance in enhancing trust between the administration and citizens and achieving good governance. The study also examined the role of transparency in reducing administrative corruption by establishing the principles of disclosure, accountability, and participation. Furthermore, it addressed the relationship between transparency and the concept of open government, which is based on promoting openness and expanding citizen participation in decision-making, benefiting from technological development and modern means of communication. The requirements for applying transparency and the obstacles that may confront it within administrative institutions were also highlighted. Results: The study concluded that activating administrative transparency represents an urgent necessity for achieving sustainable development, by improving the quality of administrative performance, consolidating the principle of accountability, and enhancing citizens' trust in state institutions. Novelty: Furthermore, it addressed the relationship between transparency and the concept of open government, which is based on promoting openness and expanding citizen participation in decision-making, benefiting from technological development and modern means of communication.